Design of the Optimal Trial of Combination Therapy - Cappola, Anne R. (Frontiers in Endocrinology, 2020)
Patients who take levothyroxine monotherapy to treat hypothyroidism frequently experience residual symptoms despite TSH testing at target levels. Trials have been conducted to evaluate the potential benefit of combination therapy with levothyroxine and liothyronine, though results have not consistently demonstrated benefit. In addition to randomization, placebo-control, and masking, four additional design choices to consider include the study population, dosing strategy for levothyroxine and liothyronine, primary and secondary outcome selection, and statistical power. A thoughtful design that considers these features will increase the likelihood that a combination trial will be considered definitive and finally resolve the important question of whether combination therapy with levothyroxine and liothyronine is a better thyroid replacement strategy than levothyroxine monotherapy.